Time-Independent Finite Difference and Ghost Cell Method to Study Sloshing Liquid in 2D and 3D Tanks with Internal Structures (Communications in Computational Physics, 2020)
A finite difference scheme with ghost cell technique is used to study viscous fluid sloshing in 2D and 3D tanks with internal structures. The Navier-Stokesequations in a moving coordinate system are derived and they are mapped onto atime-independent and stretched domain. The staggered grid is used and the revisedSIMPLEC iteration algorithm is performed. The developed numerical model is rigorously validated by extensive comparisons with reported analytical, numerical andexperimental results. The present numerical results were also validated through anexperiment setup with a tank excited by an inclined horizontal excitation or a tankmounted by a vertical baffle. The method is then applied to a number of problemsincluding sloshing fluid in a 2D tank with a bottom-mounted baffle and in a 3D tankwith a vertical plate. The phenomena of diagonal sloshing waves affected by a verticalplate are investigated in detail in this work. The effects of internal structures on theresonant frequency of a tank with liquid are discussed and the present developed numerical method can successfully analyze the sloshing phenomenon in 2D or 3D tankswith internal structures.